Carcass composition and meat quality parameters of Ghungroo pigs - THOMAS, R; BANIK, S; BARMAN, K; MOHAN, N H; SARMA, D K (The Indian Journal of Animal Sciences, 2016)
The study was part of a programme to improve pig production in India and the information on carcass composition and meat quality is very much essential towards the development of a suitable breeding plan for this pig breed. Gilts (16) and barrows (26) from Ghungroo breed were slaughtered at the age of 10 months for evaluating the different parameters. Complete dissection of carcass indicated a meat:bone ratio of 2.54 and fat:lean ratio of 0.29 for this breed. The carcass length ranged from 65.5 – 77 cm, while that of the loin eye area varied from 2.4 – 4.3 in2. Back fat thickness at three-quarters of the length of the transverse section of the exposed M. longissimus thoracis et lumborum between the 10th and 11th ribs was in the range of 2.3 - 3.85 cm. Moisture:protein ratio varied from 3.17 to 3.65 with an average of 3.45 and no significant difference was observed between gilts and barrows. The objective of the present study was to investigate the detailed carcass and meat quality parameters of Ghungroo pigs.